High Johnson’s figure of merit (8.32 THz·V) in 0.15-µm conventional T-gate AlGaN/GaN HEMTs on silicon - Ranjan, Kumud (2015)
AlGaN/GaN high-electron-mobility transistors (HEMTs) with a 0.15-µm gate were fabricated on a Si substrate with an 8-nm-thick AlGaN barrier. The device exhibited a unity current gain cutoff frequency fT of 63 GHz and maximum oscillation frequency fmax of 124 GHz. Its three-terminal OFF-state breakdown voltage BVgd is as high as 132 V. The estimated Johnson's figure of merit (=BVgd × fT) is 8.32 × 1012 V/s (8.32 THz·V), which is the highest value ever reported for a conventional SiN-passivated T-gate AlGaN/GaN HEMTs on a Si substrate without an additional field plate or gamma gate.